Intensi Konsumen dalam Menggunakan BBM yang Lebih Ramah Lingkungan berdasarkan UTAUT2 dengan Mempertimbangkan Aspek Keberlanjutan - Pangaribuan, Marvel; Sitorus, Hotna Marina (Universitas Katolik Parahyangan, 2025)
This research aims to identify the factors influencing the intention to use more environmentally friendly fuel for private vehicles. According to the regulations of the Ministry of Energy and Mineral Resources (ESDM), environmentally friendly fuel is fuel with a minimum octane rating of 91 or a minimum cetane rating of 51. Although the Indonesian government has encouraged the public to use environmentally friendly fuel, the public has not yet made this fuel their primary choice. This study examines the intention to adopt environmentally friendly fuel based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. In line with the characteristics of environmentally friendly fuel, this research enriches the UTAUT2 model with a sustainability perspective through the variables of environmental knowledge and environmental friendliness, which are the theoretical contributions of the study. The developed research model was evaluated using Partial Least Squares Structural Equation Modelling (PLS-SEM) based on 129 data collected from residents of major cities in Indonesia who refuel their vehicles. The results of this study found that environmental knowledge, habit, and price value significantly influence the public's intention to use environmentally friendly fuel. This research also offers practical contributions for stakeholders in the form of recommendations such as socialization and economic promotion to increase the use of more environmentally friendly fuel in Indonesia.